IATROGENIC URINARY TRACT TRAUMA IN OBSTETRICS AND GYNECOLOGIC SURGERIES AT H. ADAM MALIK GENERAL HOSPITAL MEDAN - Djufri, Teguh Risesa; Warli, Syah Mirsya (Indonesian Journal of Urology, 2019)
Objective: Urinary tract iatrogenic trauma in abdominal or pelvic surgery may cause morbidity, mortality, or even medico-legal problems. The close embryonic, as well as anatomical relationship between urinary tract and genital organs, may be a predisposition for urinary tract trauma, especially ureter and bladder, in obstetrics and gynecology surgeries. This research aimed to evaluate the incidence of iatrogenic urinary tract trauma in obstetrics and gynecology surgeries. Material & Methods: This was a descriptive retrospective research. This research was conducted at Urology Division of Department of Surgery at H. Adam Malik General Hospital, Medan, from February to June 2016. Total sampling method was used. Data were collected from medical records of patients who had iatrogenic urinary tract trauma due to obstetrics and gynecology surgeries at H. Adam Malik General Hospital from January 2011 to December 2015. Parameters that were evaluated included patient characteristics, the type of obstetrics and gynecology procedure that was conducted, the type of urinary tract trauma, and the type of urologic procedure conducted. Data were registered and analyzed using statistical software SPSS version 22. Results: There were 25 patients with 28 incidences of iatrogenic urinary tract trauma, which consisted of 12 iatrogenic ureteral trauma and 16 iatrogenic bladder trauma, out of all patients who underwent obstetrics and gynecologic surgeries at H. Adam Malik General Hospital, Medan, from January 2011 to December 2016. The youngest patient was 19 years old, while the oldest patient was 78 years old. Mean age of patients was 46.48 years (SD ± 11.6). The age group with the most iatrogenic urinary tract trauma was between 26-45 years old, which consisted of 12 patients (48%). Gynecologic patients had the most iatrogenic urinary tract trauma, which was experienced by 23 patients (92%). The most common diagnosis was ovarian cancer. Hysterectomy was the most common procedure to cause iatrogenic urinary tract trauma, as was found in 23 patients (92%). All patients who were found with iatrogenic bladder trauma (15 patients; 60%) underwent bladder repair. Conclusion: Gynecologic procedure, especially hysterectomy, was the most common cause of iatrogenic urinary tract trauma. Bladder repair procedure was the most common procedure performed on patients who were found with iatrogenic urinary tract trauma.